De novo Sequencing of Novel Mycoviruses From Fusarium sambucinum: An Attempt on Direct RNA Sequencing of Viral dsRNAs - Mizutani, Yukiyoshi; Uesaka, Kazuma; Ota, Ayane; Calassanzio, Matteo; Ratti, Claudio; Suzuki, Takamasa; Fujimori, Fumihiro; Chiba, Sotaro (Frontiers in Microbiology, 2021)
An increasing number of viruses is continuously being found in a wide range of organisms, including fungi. Recent studies have revealed a wide viral diversity in microbes and a potential importance of these viruses in the natural environment. Although virus exploration has been accelerated by short-read, high-throughput sequencing (HTS), viral de novo sequencing is still challenging because of several biological/molecular features such as micro-diversity and secondary structure of RNA genomes. This study conducted de novo sequencing of multiple dsRNA elements that were obtained from fungal viruses infecting two Fusarium sambucinum strains, FA1837 and FA2242, using conventional HTS and long-read direct RNA sequencing (DRS). De novo assembly of the read data from both technologies generated near-entire genomic sequence of the viruses, and the sequence homology search and phylogenetic analysis suggested that these represented novel species of the Hypoviridae, Totiviridae and Narnaviridae families. However, the DRS-based consensus sequences contained numerous indel errors that differed from the HTS consensus sequences, and these errors hampered accurate open reading frame prediction. Although with its present performance the use of DRS is premature to determine viral genome sequences, the DRS-mediated sequencing shows great potential as a user-friendly platform for a one-shot, whole-genome sequencing of RNA viruses due to its long-reading ability and relative structure-tolerant nature.